2023
DOI: 10.3390/healthcare11060909
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Neighborhood Social Capital and the Health of Chinese Urban Elderly: An Analysis Based on CHARLS2018 Data

Abstract: There is growing interest in the relationship between neighborhood social capital and the health of urban older people, but existing research still falls short in exploring the relationship between the two. Based on 2018 CHARLS data, this paper quantitatively examines the association between neighborhood social capital and the self-rated health of urban older people. The study found that, after controlling for a series of variables, both increased social interaction and increased frequency of social interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Fourteen studies (Dassopoulos et al, 2012;Hamano et al, 2010;Huang et al, 2021;Huang et al, 2023;Jiang et al, 2020;Jonsson et al, 2020;Lagaert et al, 2021;Maass et al, 2016;Mao et al, 2022;Mohnen et al, 2011Mohnen et al, , 2014Mori et al, 2022;Morozumi et al, 2020;Nieuwenhuis, 2020, 87-92) have been found that address the relationship between NSC and mental health. Some studies look at the concept of mental health in general, others at self-rated health (selfrated health [SRH], life satisfaction [LS], quality of life [QoL]) and there is one specific study for the cognitive function defined in terms of memory, recall and retrieval (Jiang et al, 2020) and two for depression (Huang et al, 2023;Mao et al, 2022). The populations studied include students, adolescents, adults, elderly and pregnant women (Table 2).…”
Section: Relationship Between Csa and The Psychological Health Of The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies (Dassopoulos et al, 2012;Hamano et al, 2010;Huang et al, 2021;Huang et al, 2023;Jiang et al, 2020;Jonsson et al, 2020;Lagaert et al, 2021;Maass et al, 2016;Mao et al, 2022;Mohnen et al, 2011Mohnen et al, , 2014Mori et al, 2022;Morozumi et al, 2020;Nieuwenhuis, 2020, 87-92) have been found that address the relationship between NSC and mental health. Some studies look at the concept of mental health in general, others at self-rated health (selfrated health [SRH], life satisfaction [LS], quality of life [QoL]) and there is one specific study for the cognitive function defined in terms of memory, recall and retrieval (Jiang et al, 2020) and two for depression (Huang et al, 2023;Mao et al, 2022). The populations studied include students, adolescents, adults, elderly and pregnant women (Table 2).…”
Section: Relationship Between Csa and The Psychological Health Of The...mentioning
confidence: 99%
“…This relationship is strongest in neighborhoods of greater deprivation. Overall, higher levels of NSC are related to better mental health (Hamano et al, 2010;Mohnen et al, 2014;Morozumi et al, 2020;Nieuwenhuis, 2020), better RSH (Huang et al, 2023;Lagaert et al, 2021;Maass et al, 2016;Mohnen et al, 2011), higher LS (Dassopoulos et al, 2012., Maass et al, 2016Mohnen et al, 2011), lower depression (Mori et al, 2022), and increased individual or collective neighborhood QoL (Dassopoulos et al, 2012;Mori et al, 2022). Only significant relationships or influences between NSC and subjective health status were controversial.…”
Section: Relationship Between Csa and The Psychological Health Of The...mentioning
confidence: 99%